Anaphora and coreference resolution : a review - Sukthanker, Rhea (2022)
Coreference resolution aims at resolving repeated references to an object in a document and forms a core component of natural language processing (NLP) research. When used as a component in the processing pipeline of other NLP fields like machine translation, sentiment analysis, paraphrase detection, and summarization, coreference resolution has a potential to highly improve accuracy. A direction of research closely related to coreference resolution is anaphora resolution. Existing literature is often ambiguous in its usage of these terms and often uses them interchangeably. Through this review article, we clarify the scope of these two tasks. We also carry out a detailed analysis of the datasets, evaluation metrics and research methods that have been adopted to tackle these NLP problems. This survey is motivated by the aim of providing readers with a clear understanding of what constitutes these two tasks in NLP research and their related issues.